A história da disciplina literatura no ensino secundário brasileiro e as avaliações externas : o exame vestibular, o ENEM e o Enade de letras - Tiuman, Patrícia Elisabel Bento (2017)
The purpose of this study was to investigate the public at whom the literary knowledge is currently aimed as well as answer the following research question: Does the fact that literary texts are constituted as programmatic contents in the National High School Exam (ENEM), in college entrance exams (vestibulares) and that they are presented in official documents ensure that their teaching occurs as expected in such documents? The study adopted a qualitative perspective, instrumented by bibliographical and documentary research. Among the theoretical reference used, we highlight the following: Haidar (1972), Romanelli (1991), Razzini (2000; 2010), Ledesma (2010), Chervel (1990) and Goodson (1991, 1995). Over the researching process, we studied the laws that have ruled the Literature curriculum of Brazilian secondary school from Pombaline Reforms to the current High School reform proposed in 2016 through the Provisional Measure 746/2016 in order to understand the insertion and the status of Literature contents in the government norms in relation to the own organization and nature of this level of education. The examination of these official documents that determine and normalize the curriculum of High School related to the theoretical understanding on the reading of literary texts presented in the documents guided the analyses of external evaluations, namely, vestibular, ENEM and the National Exam of Letras Portuguese Students (Enade). The results of this study indicated that, in ENEM's questions, although literary texts were used, the approach did not evaluate the candidate's knowledge on the specificities of aesthetic discourse or the integral reading of literary texts. Regarding vestibular, whose chosen corpus was one of a public university in Maringá (UEM), it was observed that the questions presented a more specialized approach to literary reading and, especially, the complete reading of the literary works described in the Candidate Handbook. The questions expected the candidate to understand the specificities of the aesthetic discourse and the characteristics of literary schools, which are part of the Literature curriculum in high school. However, the questions disregarded deeper aspects of literary reading such as the de-automation of habits, critical formation, acculturation and socialization of the reader. As regards Enade, there was an emphasis on theory, both in the area of Linguistics and Literature. This exam presupposed the specialized reading of works representative of Brazilian and Universal Literature, the domain of didactics, theories related to teaching and educational legislation. In sum, even though ENEM presented Literature as an assessing content, in reality, the questions revolved reading practices that are similar to the reading of non-literary texts, since the specificities of literary reading were not contemplated. On the other hand, the questions of vestibular and Enade demanded the study of the specificities of aesthetic discourse and the integral reading of literary texts. Nevertheless, not always the approach produced by the questions allowed the presupposed reading to surpass the compositional aspects of the works in order to lead to an interpretation in which the vision of the world, the man and the society printed in the aesthetic object could be contemplated, supplanting the cataloging of theoretical categories. Therefore, if such exams do not evaluate the specificities of aesthetic discourse the tendency is that Literature loses its function within the curricula of High School.